Use of homeopathic preparations in experimental studies with healthy plants - Majewsky, Vera; Arlt, Sebastian; Shah, Devika; Scherr, Claudia; Jaeger, Tim; Betti, Lucietta; Trebbi, Grazia; Bonamin, Leoni [UNESP]; Klocke, Peter; Baumgartner, Stephan (Elsevier B.V., 2009)
Background. The last comprehensive review of experimental research on effects of homeopathic treatments on plants was published in 1984, and lacked formal predefined criteria to assess study quality. Since then several new studies with more advanced methods have been published.Objectives: To compile a review of the literature on basic research in homeopathy with healthy plants with particular reference to studies investigating specific effects of homeopathic remedies.Methods: The literature search included English, French, German, Italian, Portuguese and Spanish publications from 1920 to April 2009, using predefined selection criteria. We included experiments with healthy whole plants, seeds, plant parts and cells. The outcomes had to be measured by established procedures and statistically evaluated. We developed a Manuscript Information Score (MIS) and included only publications which provided enough information for proper interpretation (MIS >= 5). A formallised Study Methods Evaluation Procedure (SMEP) was used to evaluate these studies, and the subgroup of studies with adequate controls to identify specific effects.Results: A total of 86 studies in 79 publications was identified, 43 studies included statistics, 29 had MIS >= 5, and 15 studies investigated the specificity of homeopathic preparations. Specific effects of decimal, centesimal and fifty millesimal potencies were found including dilution levels far beyond the Avogadro number. In consecutive series of potencies only some of the tested potencies showed effects. There were many individual studies with diverse methods and very few reproduction trials.Conclusions: Healthy plant models seem an useful approach to investigate basic research questions about the specificity of homeopathic preparations. More investigations with more advanced methods are recommended, especially in the sectors of potentisation techniques, effective potency levels and conditions for reproducibility. Systematic negative control experiments should become a routine procedure to control the stability of the experimental systems. Homeopathy (2009) 98, 228-243.
Keywords: Review; Basic research; Homeopathy; Potentisation; Potentised dilutions